(untitled) (Development Service Industry Management, 2025)
In order to ensure the coordinated activities of research and development institutions and to reduce the uncertainty of technology commercialization, an advanced tool for verifying technology development decisions in the early stages of commercialization, i.e., a tool for assessing the commercial potential of a technology, is needed. The purpose of the article is to determine the importance of the factors of the commercial potential of technologies with the help of expert research. To achieve the goal, the following tasks were approached: on the basis of the created system of factors of the commercial potential of technologies, conduct an expert study aimed at gathering information about the importance of factors in technologies; apply the methods of mathematical statistics to determine the level of compatibility of expert opinions and the significance of factors. The system of factors of the commercial potential of technologies and the identified significance of the factors can be used as reference points for technology developers, investors and potential owners in the decision-making process regarding the commercialization, investment or purchase of technology, as well as during the next research stage of developing a model for assessing the commercial potential of technologies. In today’s world, transnational corporations (TNCs) are key players in the field of foreign economic relations and the main driving force of the integration of the global economy. TNCs are huge financial and industrial conglomerates, which can be both national and international in terms of their capital. They are organized according to the principle of global planning and management and participate in the international division of labor, taking advantage of internationalization to maximize their profits. In the era of globalization, characterized by the integration of markets and the international orientation of TNCs, the marketing strategies of these companies are, in their essence, internationalization strategies. They can be implemented at different levels - from intra-corporate to inter-corporate. Companies not only export domestically produced products and services and use raw materials and semi-finished products from other countries, but also invest in overseas production and sales facilities and establish research and development centers abroad. Centralized services such as programming, accounting and design can also be outsourced. In addition, financing of both domestic and foreign projects can be carried out at the expense of foreign sources.